Comparing efficacy and safety of fibrinogen concentrate to cryoprecipitate in bleeding patients: a systematic review. Issue 8 (24th April 2016) - Jensen, N. H. L.; Stensballe, J.; Afshari, A.
Abstract : Background: Bleeding is associated with the depletion of fibrinogen, thus increasing the risk of coagulopathy, further bleeding and transfusion requirements. Both fibrinogen concentrate and cryoprecipitate replenish low plasma fibrinogen levels. This systematic review aims to identify and evaluate evidence of efficacy and safety of fibrinogen concentrate and cryoprecipitate in bleeding patients. Method: Cochrane Central Register of Controlled Trials (CENTRAL), Medline, EMBASE up to 2nd of March 2015 were among the electronic search strategies of randomized controlled trials and non‐randomized studies with meta‐analysis employed. Studies for inclusion required bleeding patients being treated with either fibrinogen concentrate or cryoprecipitate. Mortality was the primary endpoint. Secondary outcomes included bleeding, coagulopathy, transfusion requirements and clinical complications related to the intervention. PRISMA methodology, a data‐extraction form and the Cochrane risk of bias tool were all employed. Results: Four studies were eligible for inclusion in this systematic review; one randomized controlled trial (RCT) consisting of 66 patients and three observational studies involving 218 patients in total. No mortality was reported in the published papers. There were no differences in fibrinogen‐level increase, bleeding, RBC transfusions or thromboembolic complications. The RCT showed a possible increased functional improvement of haemostasis after cryoprecipitate therapy compared to fibrinogen concentrate. Conclusion: The available evidence directly comparing fibrinogen concentrate to cryoprecipitate is sparse and with high risk of bias. Recommendation of one product over the other for fibrinogen substitution in the bleeding patient with acquired hypofibrinogenaemia is currently not possible. Future research should guide us towards evidence‐based decisions of product superiority.